“The best place we can learn from is ourselves”the Development, Implementation and Use of an Online Patient-based Community of Practice for People with Type 2 Diabetes - Glenn Mason (Adult Education Research Conference, 2015)
This paper reports on the development, implementation and use of a patient-centred online community of practice for people with type 2 diabetes mellitus. In this qualitative study, the theoretical framework of activity theory is adopted to describe the complexity of the use of the system and to frame the evaluation of the use of the learning environment.
Keywords: learning design; activity theory; design-based research; patient-centred learning; type 2 diabetes; transformative learning